THE MYRMICINE ANT GENUS ALLOMERUS MAYR (HYMENOPTERA: FORMICIDAE) - FERNÁNDEZ FERNANDO (Caldasia)
The Neotropical myrmicine ant genus Allomerus Mayr is revised. The genus is apparently monophyletic based on the antennal club confi guration. I recognize 8 species (4 described as new): Allomerus brevipilosus n. sp. (Brazil), A. decemarticulatus Mayr (Brazil, French Guiana), A. dentatus n. sp. (Venezuela), A. maietae n. sp. (Brazil), A. octoarticulatus Mayr (=A. tuberculatus Forel n. syn. = A. octoarticulatus var. demerarae W. M. Wheeler n. syn. = A. novemarticulatus Wheeler & Mann n. syn. [Brazil, Bolivia, Colombia, French Guiana, Peru]), A. septemarticulatus Mayr status rev. (Brazil), A. undecemarticulatus n. sp. (Venezuela) and A. vogeli Kempf (Venezuela, Brazil). Better knowledge of the taxonomy of Allomerus is needed to understand the apparently sporadic differences in antennal fl agellomere number and speciation processes that are probably linked to plant cavity colonization.